1998
DOI: 10.1002/(sici)1099-1611(199803/04)7:2<112::aid-pon300>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Depressive disorders in an out­patient oncology setting: prevalence, assessment, and management

Abstract: Objective. To assess the prevalence of depressive disorders among cancer patients attending the out‐patient oncology clinic of a major hospital, and to initiate the development of a valid and practical psychological morbidity screening instrument suitable for local conditions. Design. Survey utilising self‐report screening scales and full psychiatric interviews. Setting. Radiotherapy department, Groote Schuur Hospital. Patients. Breast cancer, head and neck cancer, and lymphoma patients attending out‐patient o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
2
7

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(74 citation statements)
references
References 15 publications
5
60
2
7
Order By: Relevance
“…Each item in HADS was rated on a fourpoint scale giving maximum score of 21. Scores were divided into four ranges: normal (0-7), mild (8-10), moderate (11)(12)(13)(14)(15), and severe (16)(17)(18)(19)(20)(21) depression.…”
Section: Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…Each item in HADS was rated on a fourpoint scale giving maximum score of 21. Scores were divided into four ranges: normal (0-7), mild (8-10), moderate (11)(12)(13)(14)(15), and severe (16)(17)(18)(19)(20)(21) depression.…”
Section: Methodssupporting
confidence: 85%
“…In this study, the prevalence of depression (detected by HADS) was found in 51.9% of patients higher than that reported by other authors [18][19][20]. This result supports the need to screen patients with cancer for depression to provide early intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results confirmed this evidence and also agreed that lowering the cutoff from 11 to 8 may decrease the rate of misclassification. As previously suggested by Berard and colleagues [2], the cutoff of 8 could lead to a higher rate of misclassification (false positive). Actually, in the sample in this study, the number of false-positive classifications of depressed patients increased from one to three when moving the HADS cutoff from 11 to 8.…”
Section: Discussionmentioning
confidence: 99%
“…Berard et al 1998;Fallowfield et al 2001;Kruse et al 1999;Söllner et al 2001 Helgeson et al 1999Helgeson et al , 2001.…”
Section: Interventionen Zur Verbesserung Der äRztlichen Psychosozialementioning
confidence: 99%